Workplace incivility and its causes among nurses in andaman and nicobar islands - DR. GIGI G.S; KUMARI, MS. JAYA (The journal of contemporary issues in business and government, 2020)
Workplace incivility is one of the major concerns in the healthcare industry. The objective of the study is to understand the concept of workplace incivility, to examine the factors causing workplace incivility, to examine the various steps to eliminate workplace incivility, to find out the influence of demographic variables on workplace incivility and to give suggestions to the targets to cope up with workplace incivility. Descriptive, exploratory and casual research methodology is used, the statistical tools used for analysis are frequency analysis, mean analysis and one way ANOVA. The key cause for workplace incivility among nurses was found to be physicians, and none of the demographic variables such as age, gender, and work experience, hospital location, marital status, and qualification affected workplace incivility.